Desarrollo de destrezas con criterio de desempeño en el área de matemática - Naranjo Porras, Julio César (2017)
Education in Ecuador is a means of impulse that nowadays it finds considering changes, to which teachers are immersed to carry out the correct academic instruction, such as the development of skills with performance criteria, being the beginning of a permanent change. This research had as a general objective to determine the incidence of the skills in the mathematics subject, which show the concretion of the learning level of the students in their cognitive, procedural and attitudinal development that improve their knowledge. The structure of the research is based on the development skills in the mathematics subject based on theoretically, scientifically and methodological procedure employed, which leads to the determination of results that it results in conclusions and recommendations. The national curriculum it projects the achievement of objectives that are reflected in the skills with performance criteria that finally it shows in the interest on the part of the students, which contributes to the integral development of these with the direct participation from teachers, authorities and parents at Rosa Zarate Educational unit from Salcedo canton.